Patient safety in Europe: challenges and opportunities (Italian Journal of Public Health, 2005)
Healthcare has been relatively slow in comparison to other industries to recognize itself as a high risk activity. Recent estimates suggest that 1 in 10 patients admitted to hospital experience some form of unintended harm. In both human and economic terms, the need to reduce these unacceptable levels of harm is impossible to ignore. Patient safety is a serious concern for many EU Member States.This has been given impetus by both the UK and Luxembourg Presidencies of the European Union, both of which have made patient safety a headline health priority theme.The overriding aims of patient safety activity during the UK Presidency have been to ensure that: • patient safety becomes a key priority on the European health agenda, both at EU level and in individual Member States there are concrete mechanisms and practical programmes of activity established at the EU level to take forward patient safety issues • Activity at the European level also aims to build upon the programme established by the World Health Organization through the World Alliance for Patient Safety and the work of other key partners.Much remains to be done to achieve safer care for patients across Europe. Action at the European level has a vital role to play in ensuring that safe care is a core part of health system improvements in all countries. Safe care can never be an optional extra; it is the right of every patient who entrusts their care to our health care systems.
Keywords: Healthcare policy; patient safety; risk management; adverse event; medical error; Europe